The Prevalence And Risk Factors Of Cognitive Dysfunction In Patients With Diabetes Mellitus In Iraq - Najim, Hafsa S. (2013)
Diabetes mellitus is a chronic metabolic disease that is distinguished by many complications. It is mainly a self-managed disease that needs intact cognition to maintain better quality of life. Cognitive dysfunction is a neurodegenerative changes that might be associated with diabetes mellitus. It is considered as the first stage of dementia and Alzheimer disease which is together with diabetes are global growing prevalence health concerns. This study investigates the unclear relationship between diabetes mellitus and cognitive dysfunction. It deals with occurrence of cognitive dysfunction among diabetes. It also compares the occurrenceof cognitive impairment in type 1 and type 2 diabetes. In addition, it investigates the influence of diabetes as a chronic disease, its complication and treatment on cognitive performance. A comparative cross-sectional methodology was adopted to achieve the study objectives. Two tools were used to evaluate cognitive dysfunction, the Mini-Mental Status Examination (MMSE), and Montreal Cognitive Assessment (MoCA). After calculating sample size, 380 patients with diabetes, and 100 control subjects who met inclusion and exclusion criteria were included in the study. As a sub-study, the association between brain magnetic resonance imaging (MRI) marker status and cognitive performance was assessed for certain number of participants (n=10 per arm). The major findings of this study are that according to MMSE, the prevalence of cognitive dysfunction was 16.3% of patients with diabetes and 7% of controls.